EFEKTIVITAS DESAIN PEMBELAJARAN TERPADU BERBASIS CORE CONTENT DI SEKOLAH DASAR - Een Y. Haenilah (Universitas Negeri Malang, 2017)
Abstract: This study intends to explore the effectiveness of integrated learning design based on core content from the development of Elementary School 2013 Curriculum. This study employed quasi experiment design. The population of this study was a school which implements 2013 Curriculum in Bandar Lampung. The samples were teachers and students. The instruments for obtaining data are a test, interview, observation, and documentation. The data analysis of this study used t-test. The results showed that the integrated learning design based on core content is effective in establishing a good condition of learning which generate an integrated knowledge and integrated social within experience and exercise integration. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan efektivitas desain pembelajaran terpadu berbasis core content pengembangan dari kurikulum 2013 SD. Desain penelitian menggunakan quasi eksperimen. Populasi penelitian adalah sekolah yang sudah menggunakan kurikulum SD 2013 di Bandar Lampung. Sampel penelitian adalah guru dan siswa. Alat pengumpul data menggunakan tes, wawancara, observasi dan dokumentasi. Analisis menggunakan t-test. Hasil membuktikan bahwa desain pembelajaran terpadu berbasis core content efektif menciptakan aktivitas pembelajaran yang menghasilkan keterpaduan kemampuan pengetahuan, keterpaduan sosial dalam keterpaduan pengalaman dan latihan.